PELAKSANAAN PEMILIHAN UMUM KEPALA DAERAH DI DAERAH YANGBERKARAKTERISTIK KEPULAUAN (Studi Kasus Pemilihan Umum Kepala Daerah Di Provinsi Maluku) - Julista Mustamu (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Maintaining the holding of regional head elections (post-conflict local elections)inregional areas that are characterized by islands in Indonesia that are in accordance withthe characteristics of the island community is in the context of realizing fair and beneficialpost-conflict local election implementation for the community, to further improve welfareand adapted to the development of the island community. In Law No. 1 of 2015 concerningDetermination of Government Regulations in lieu of Law No. 1 of 2014 concerning theElection of Governors, Regents, and Mayors not being able to accommodate theostconflict local election that is in favor of the regions characterized by islands. Therefore,in the implementation of post-conflict local election in the islands, there are still variousproblems related to the implementation of post-conflict local elections. Thus, legalarrangements are needed that favor the regions that are characterized by islands. Wherethe government is obliged to treat the people of the island province in a different way fromother provinces, considering the sea has special characteristics that are different from theland. The research method used is normative legal research. The problem examined is howis the implementation of general elections in regional areas characterized by islands,especially in Maluku province? The results of this study are that in organizing generalelections in areas characterized by islands, especially in Maluku province, there are stillseveral problems. As related to the involvement of police officers and the State CivilApparatus (ASN), weak supervision, and the obstruction of the distribution of ballots, andthe delay in the results of recapitulation of election results. This is because MalukuProvince is an island characterized by islands, where there are many small islands thatare difficult to reach either by the executor or the election supervisor. Although at the timeof voting it was generally safe and conducive.